Edukasi Kesehatan Preventif Berbasis Syariat Islam Melalui Program Remaja Cerdas dalam Pencegahan Pergaulan Bebas: Preventive Health Education Based on Islamic Sharia Through the ‘Smart Teenagers’ Programme in the Prevention of Promiscuity - Musriwan Musriwan; Andi Dahmayanti; Risdayani Risdayani (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2026)
Promiscuity among teenagers is one of the issues that can have a negative impact on reproductive health, moral development, and the future of the younger generation. Preventive measures need to be implemented through education that integrates health aspects and Islamic values so that teenagers have a better understanding and awareness of how to avoid risky behaviour. This community service activity aims to provide education and raise awareness among adolescents to prevent promiscuity through preventive health education based on Islamic Sharia law via the CERDAS (Prevent Risks, Self-Education, Anti-Promiscuity) Youth Programme. The activity was carried out at UPT SMKN 4 Takalar by students participating in the Practical Work Study (KKN) programme from the Islamic Institute (IAI) STIBA Makassar. The material was delivered through lectures, question-and-answer sessions, and interactive discussions covering adolescent reproductive health, the dangers of promiscuity, risky sexual behaviour, and the reinforcement of Islamic Sharia values in preserving personal dignity and the honour of one’s lineage. The results of the activity demonstrated high levels of enthusiasm and participation among attendees throughout the educational process. The programme successfully educated participants on the risks of promiscuity and fostered moral and religious awareness to adopt healthy social behaviour in accordance with Islamic teachings. The ‘CERDAS’ Youth Programme has the potential to serve as an effective model for preventive health education based on Islamic Sharia in building a healthy, principled, and virtuous younger generation.